Daily dynamics of cortisol in female students with somatoform dysfunction of the autonomic nervous system engaged in fitball-gymnastics - E.A. Milashechkina; T.I. Jandarova; E.I. Rusanova; E.V. Mitina (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the impact of the fitball-gymnastics course on the daily dynamics of the cortisol concentration of female students with a disorder of the autonomic nervous system. Methods and structure of the study. The scientific work was carried out at the North Caucasian Federal University, the participants were female students assigned to a special medical group with hypertonic (n=14) and hypotonic (n=16) type of vegetovascular dystonia at the age of 18-20 years. Control group - practically healthy female students (n=28). As a leveling of the processes associated with the disease, a course of fitball-gymnastics exercises was used in the system of additional education. Female students with ADHD of hypertonic type (n=15) and hypotonic type (n=17) made up correction groups. A highly sensitive competitive immunoassay was used to measure cortisol concentration in human saliva plasma. To determine daily fluctuations, hormone sampling was performed at 8:00, 12:00, 16:00 and 20:00. Results and conclusions. As a result of the experiment, violations of the daily secretion of cortisol were revealed in girls with ADHD both in hypotonic and hypertonic types. In female students with ADHD of the hypotonic type, the cortisol concentration increased by the end of the day, in female students with ADHD of the hypertonic type, the maximum values were determined at 12 o'clock. Students with ADHD involved in fitball gymnastics showed a positive dynamics of cortisol concentration during the day - they revealed a decrease in its concentration in the evening.